2017
DOI: 10.1073/pnas.1701196114
|View full text |Cite
|
Sign up to set email alerts
|

SAGA complex mediates the transcriptional up-regulation of antiviral RNA silencing

Abstract: Pathogen recognition and transcriptional activation of defenserelated genes are crucial steps in cellular defense responses. RNA silencing (RNAi) functions as an antiviral defense in eukaryotic organisms. Several RNAi-related genes are known to be transcriptionally up-regulated upon virus infection in some host organisms, but little is known about their induction mechanism. A phytopathogenic ascomycete, Cryphonectria parasitica (chestnut blight fungus), provides a particularly advantageous system to study RNAi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 63 publications
(98 reference statements)
2
38
0
1
Order By: Relevance
“…Infection of Plant Pathogenic Fungi with Viroids. We investigated the possibility of viroid infection in three phytopathogenic ascomycete fungi, Cryphonectria parasitica, Valsa mali, and Fusarium graminearum, which are the causative agents of chestnut blight, apple tree canker, and wheat/barley head blight and maize ear rot diseases, respectively (46)(47)(48). Spheroplasts prepared from these three fungi were transfected with in vitro RNA transcripts derived from each of the seven viroid cDNA clones and then regenerated and followed by subcultures (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Infection of Plant Pathogenic Fungi with Viroids. We investigated the possibility of viroid infection in three phytopathogenic ascomycete fungi, Cryphonectria parasitica, Valsa mali, and Fusarium graminearum, which are the causative agents of chestnut blight, apple tree canker, and wheat/barley head blight and maize ear rot diseases, respectively (46)(47)(48). Spheroplasts prepared from these three fungi were transfected with in vitro RNA transcripts derived from each of the seven viroid cDNA clones and then regenerated and followed by subcultures (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of the budding yeast, Saccharomyces cerevisiae, ∼10% of all genes have been reported to be under the control of SAGA (27,28). Our previous study showed HAT activity, but not DUB activity, to be a major player in the SAGA-mediated induction of dcl2 upon viral infection in C. parasitica (21). HAT activity, as a major contributor, and DUB activity as a minor contributor, are involved in the SAGAmediated up-regulation of agl2 (21).…”
Section: Significancementioning
confidence: 96%
“…Δp69 Infection in C. parasitica. Using a genetic screening approach, we have previously shown that sgf73, a component of the SAGA, is essential for the high induction of antiviral RNA silencing (21). To investigate whether the SAGA complex is involved in transcriptional up-regulation of a wide range of genes following viral infection in C. parasitica, we analyzed the global transcriptome profiles of the CHV1-Δp69-infected Δsgf73 and DK80 (Δsgf73 parental strain) strains relative to that of the virus-free DK80 strain using high-throughput cDNA sequencing (RNA-seq) ( Fig.…”
Section: Dcl2 Is Essential For Saga-mediated Gene Up-regulation Upon mentioning
confidence: 99%
See 1 more Smart Citation
“…. 一 方, 中 国 の Jiang ら の グ ル ー プ が, gemini 様 ssDNA ウイルスや (-)RNA ウイルスが Sclerotinia sclerotiorum へ人為的導入に成功している (Liu et al, 2014;Yu et al, 2010) .また,筆者らは粒子ではなく YkV1 感染性 cDNA クローンの合成に成功した (Zhang et al, 2016 (Chiba et al, 2013a;Chiba et al, 2013b;Chiba et al, 2016;Salaipeth et al, 2014) ,その調節機構にもメスが入った (Andika et al, 2017;Chiba and Suzuki, 2015) .RNA サイレンシングが RNA ウイルスのゲノムの安定維持に正にも負にも働くことが示 された(Eusebio-Cope and Sun et al, 2009) .ま た,菌類ウイルスの RNA サイレンシング抑制蛋白質として 同定されている CHV1 の p29 が,異種ウイルスの複製,無 性胞子を通じた垂直伝搬を促進することも明らかにした (Suzuki et al, 2003) .さらに,CHV1,MyRV1 の病徴発現に 関与する宿主因子 (Faruk et al, 2008a(Faruk et al, , 2008b (Kanhayuwa et al, 2015;Zhang et al, 2016) , 菌類ウイルスの虫媒伝染 (Liu et al, 2016)あるいは菌類ウイルスの昆虫 (Liu et al, 2016) , 植物細胞 (Nerva et al, 2017)…”
unclassified